2018
DOI: 10.1177/0956797617747648
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to Effective Altruism: The Role of Subjective Preferences in Charitable Giving

Abstract: Charity could do the most good if every dollar donated went to causes that produced the greatest welfare gains. In line with this proposition, the effective-altruism movement seeks to provide individuals with information regarding the effectiveness of charities in hopes that they will contribute to organizations that maximize the social return of their donation. In this research, we investigated the extent to which presenting effectiveness information leads people to choose more effective charities. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
126
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(132 citation statements)
references
References 30 publications
5
126
1
Order By: Relevance
“…People's willingness to donate to prosocial causes is famously biased by affective influences, such as the ease of imagining an individual relative to a statistic (Small et al, 2007). Consumers often deny that one charitable cause can be objectively worthier than another (Berman et al, 2018). And even among donations to the same cause, the donation's reputational impact tends to be guided by the amount of sacrifice rather than social good (Johnson, 2020), producing little social incentive for effective giving.…”
Section: Discussionmentioning
confidence: 99%
“…People's willingness to donate to prosocial causes is famously biased by affective influences, such as the ease of imagining an individual relative to a statistic (Small et al, 2007). Consumers often deny that one charitable cause can be objectively worthier than another (Berman et al, 2018). And even among donations to the same cause, the donation's reputational impact tends to be guided by the amount of sacrifice rather than social good (Johnson, 2020), producing little social incentive for effective giving.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were randomly assigned to one of the three scenarios: Worse Hybrid (WH), Better Hybrid (BH), and Dominant Hybrid (DH). Each participant was given a monetary endowment of $2 to allocate across the investment options available in their assigned scenario, with outcomes for each option presented in plain and consistent language (Berman, Barasch, Levine, & Small, ) . Social benefit was operationalized as the provision of iodized salt to poor populations, and all participants viewed a brief excerpt about its social welfare implications .…”
Section: Failure To Achieve Outcome Efficiencymentioning
confidence: 99%
“…Another explanation for why people donate ineffectively is that they do not know how to do so (the belief-based explanation, or "distorted altruist" explanation, see Berman et al, 2018). In support of this explanation, it has been shown that people give less to charities with high overhead costs because they suffer from the misconception that high overhead necessarily entails low cost-effectiveness (Baron & Szymanska, 2011;Caviola, Faulmüller, Everett, Savulescu & Kahane, 2014;Gneezy, Keenan & Gneezy, 2014).…”
Section: Introductionmentioning
confidence: 99%